Multidimensional prediction of work traffic crashes among Spanish professional drivers in cargo and passenger transportation. Issue 1 (2nd January 2022) - Useche, Sergio A.; Cendales, Boris; Alonso, Francisco; Montoro, Luis
Abstract : The aim of this study was to examine the effect of different environmental, mechanical and individual factors associated with fatalities and serious injuries caused by work traffic accidents among cargo and passenger transport drivers (CPTD) in Spain. For this cross-sectional study, national data on work traffic accidents collected in Spain during the last 3 years were analyzed through a regression modeling approach, in order to predict the severity of traffic crashes involving CPTD. Using binary logistic regression analyses, it was found that the type of road and accident, the meteorological, light and vehicle conditions, individual characteristics and risky driving behaviors significantly predict the risk of fatal work traffic accidents and serious injuries. These findings highlight the importance of combining organizational efforts with national road safety policies in order to generate a traffic safety culture among CPTD.